Assessment of marine geoid models by ship-borne GNSS profiles - Varbla, Sander; Ellmann, Artu; Märdla, Silja; Gruno, Anti (Geodesy and Cartography, 2017)
Even though the entire Baltic Sea is included in previous geoid modelling projects such as the NKG2015 and EGG07, the accuracy of contemporary geoid models over marine areas remains unknown, presumably being offshore around 15–20 cm. An important part of the international cooperation project FAMOS (Finalising Surveys for the Baltic Motorways of the Sea) efforts is conducting new marine gravity observations for improving gravimetric quasigeoid modelling. New data is essential to the project as the existing gravimetric data over some regions of the Baltic Sea may be inaccurate and insufficiently scarce for the purpose of 5 cm accuracy geoid modelling. Therefore, it is important to evaluate geoid modelling outcome by independent data, for instance by shipborne GNSS measurements. Accordingly, this study presents results of the ship-borne marine gravity and GNSS campaign held on board the Estonian Maritime Administration survey vessel “Jakob Prei” in West-Estonian archipelago in June/July 2016. Emphasis of the study is on principles of using the GNSS profiles for validation of existing geoid models, post-processing of GNSS raw data and low-pass filtering of the GNSS results. Improvements in geoid modelling using new gravimetric data are also discussed. For example, accuracy of geoid models including the new marine gravity data increased 11 mm as assessed from GNSS profiles. It is concluded that the marine GNSS profiles have a potential in providing complementary constraints in problematic geoid modelling areas.